Glutathione Transferase (GST)-Activated Prodrugs - Andrea Calderan; Paolo Ruzza (MDPI AG, 2013)
Glutathione transferase (formerly GST) catalyzes the inactivation of various electrophile-producing anticancer agents via conjugation to the tripeptide glutathione. Moreover, several data link the overexpression of some GSTs, in particular GSTP1-1, to both natural and acquired resistance to various structurally unrelated anticancer drugs. Tumor overexpression of these proteins has provided a rationale for the search of GST inhibitors and GST activated cytotoxic prodrugs. In the present review we discuss the current structural and pharmacological knowledge of GST-activated cytotoxic compounds.